Currículo-corpo em giro deculonial: raça-gênero-sexualidades entre cruzos corporeográficos - Silva, Leonardo dos Santos (2024)
This thesis isn't about the curriculum, it's about a curriculum. It is about the erasure of conceptual notions that make thought operate and our judicious ways of configuring discursive and [anal]ical practices on and in the body. So the question is: how can a body-curriculum claim a corporeography permeated by race-gender-sexuality in matrices of anal and deculonic politics? To this end, some assumptions from queer theory ( Spargo, 2017), quare analytics (Jonhson, 2020), language (Austin, 1990), decolonial studies Wallerstein (1992); Oliveira; Lucini (2021); Quijano (2009); Oliveira, V. (2022); Restrepo; Martinez (2010); Mignolo (2017); Walsh (2009), anal politics (Vidarte (2019); Saez and Carrascosa (2016); Preciado (2022)) intersect in post-critical methodological corners (Paraíso, 2012), and in the methodological finding “epistemic orgy”, fluid exchanges are established with the Jacaré, Vera Verão and Lacraia. In an epistemic erasure with the notion of corporeography, racegender-sexualities are undertaken in their co-formations and coproductions, with the “death” of queer evoking and penetrating a curriculum-body in a deculonial turn. In the meantime, the thesis is defended: the curriculum-body stands out for its insubmission, being in the presentified making of the body and through corporeography with racegender-sexuality materialities, which makes it a chance to slide territories and crosses in the deculonial turn. What this body-curriculum promotes is crisis and, as it is an inexhaustible source of invention, it creates tools that provoke disquiet and slippage so that we can think about, understand and live the body at crossroads. What this turn promotes is a change in [analytical] posture. The deculonial turn operates by blurring the temporalities and spatialities of the ass, on the verge of transforming the renegades into co-producers and co-formers of curricular crossroads. In this turn, decoloniality starts from the center of the ass, in a recurrence of the removal of gender, sexualities, races, social class from an immutable and unproductive configuration. The spelling of the body, the ass, the curriculabodies establish sociocultural surubas inherent to the implosions caused in the body, with the body and for the body